2014
DOI: 10.1152/ajpheart.00787.2013
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic blockade enhances coronary vasoconstrictor response to forehead cooling

Abstract: Forehead cooling activates the sympathetic nervous system and can trigger angina pectoris in susceptible individuals. However, the effect of forehead cooling on coronary blood flow velocity (CBV) is not well understood. In this human experiment, we tested the hypotheses that forehead cooling reduces CBV (i.e., coronary vasoconstriction) and that this vasoconstrictor effect would be enhanced under systemic β-adrenergic blockade. A total of 30 healthy subjects (age range, 23-79 years) underwent Doppler echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Alternatively, older men may have augmented ␣-adrenergic coronary vasoconstrictor responses during exercise compared with young men, which would dampen coronary vasodilation. However, we recently showed that coronary vasoconstriction to noxious forehead cooling was comparable between young and older adults (45). Whether ␣-adrenergic coronary vasoconstriction is enhanced in older men during exercise is unknown.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Alternatively, older men may have augmented ␣-adrenergic coronary vasoconstrictor responses during exercise compared with young men, which would dampen coronary vasodilation. However, we recently showed that coronary vasoconstriction to noxious forehead cooling was comparable between young and older adults (45). Whether ␣-adrenergic coronary vasoconstriction is enhanced in older men during exercise is unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Isoproterenol is a nonselective ␤-AR agonist with a short half-life (Ͻ2 min) that has been previously used by our laboratory (44,45) and others (5,42,49) to challenge the extent of ␤-AR blockade with propranolol. In the current study, intravenous propranolol completely blocked the tachycardia response to the peak dose of intravenous isoproterenol, indicating a full ␤-AR blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary outcome variable was the ΔCBV to ΔRPP ratio from baseline to exercise, which was calculated as ΔCBV/ΔRPP × 1000. This ratio has been used previously to quantify coronary hyperemia normalized to cardiac metabolism; higher numbers indicate greater myocardial O 2 supply relative to demand [3033]. Statistical analysis was performed using SPSS 22.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to each stressor, three resting BPs were obtained by automated oscillometry of the right brachial artery (Philips Sure Signs VS3) after 15 min of quiet rest and these were used to verify the Finometer values as previously described (Muller et al. ). All beat‐by‐beat variables were collected at 200 Hz by PowerLab (ADInstruments).…”
Section: Methodsmentioning
confidence: 99%